Nudging: An Experiment on Transparency, Controlling for Reactance and Decision Time - Tobias Schütze; Carsten Spitzer; Philipp C. Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2023)
Is being informed about nudging detrimental to the effect of the nudge? This paper reports results from an experimental study (n = 623) testing the effects of transparency on the effectiveness of a default nudge while controlling for reactance and decision time. Overall, the data show that more people follow the default if the nudge is made transparent. More importantly, though, effects of transparency differ depending on whether people are fast or slow in their decision making. In particular, (only) slow decision makers react more positively (keeping the default) if nudging is made transparent. Moreover, the data also show an interaction of reactance and decision time in that more reactant subjects making slower decisions respond more negatively (i.e. leave the default more often). Thus, a positive effect of transparency as well as a negative impact of reactance can be established in the data if decision time is accounted for.
Keywords: C90; D90; D91; 330; nudging; transparency; reactance; decision time